2021
DOI: 10.3389/fonc.2021.773905
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGF Therapy in Refractory Pituitary Adenomas and Pituitary Carcinomas: A Review

Abstract: Most pituitary tumors are considered benign adenomas, and only 0.1%–0.2% of them present metastasis and are defined as pituitary carcinomas (PCs). Refractory pituitary adenomas (PAs) lie between benign adenomas and true malignant PCs and are defined as aggressive-invasive PAs, characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments. Refractory PAs and PCs are notoriously difficult to manage because of limited therapeutic options. Vascular endothelial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Angiogenesis, the formation of new blood vessels, is crucial for tumor development and metastasis [ 16 ]. Unlike most solid tumors, PitNETs are less vascularized compared to normal pituitary tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis, the formation of new blood vessels, is crucial for tumor development and metastasis [ 16 ]. Unlike most solid tumors, PitNETs are less vascularized compared to normal pituitary tissue.…”
mentioning
confidence: 99%
“…Unlike most solid tumors, PitNETs are less vascularized compared to normal pituitary tissue. Even invasive, aggressive, or malignant PitNETs do not demonstrate a significant increase in vascularity, with the exception of some rare secondary deposits of metastatic PitNETs [ 16 ]. The genetic background of low vascular density in PitNETs is unclear.…”
mentioning
confidence: 99%
“…Therefore, these reports suggested that VEGF signaling is involved in the development of AD. Previous studies indicated that inhibition of Cdk5 activity in rat pituitary cells reduced VEGF-A expression [ 63 , 64 ], implying that an underlying link exist between VEGF-A and Cdk5 in the endothelium. Interestingly, in the present study, recombinant VEGF-A directly prevented Aβ-mediated Cdk5 inhibition and promoted endothelial cell proliferation in bEnd.3 cells, and prevented brain capillary loss in an AD mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid advancement in technology has spurred extensive research into a wide array of potential biomarkers, leading to significant developments in this field [62]. These biomarkers are varied, encompassing different biochemical forms such as nucleic acids, proteins, carbohydrates, lipids, small metabolic products, Recent studies, both preclinical and clinical, have underscored the importance of anti-VEGF therapy in treating pituitary tumors [61]. In murine models, anti-VEGF agents have demonstrated significant effectiveness when used as single agents.…”
Section: The Importance Of Biomarkers In Oncologymentioning
confidence: 99%